Perubahan Konstitusi Melalui Putusan MK: Telaah Atas Putusan Nomor 138/PUU-VII/2009 - Wardaya, Manunggal K. (Jurnal Konstitusi, 2010)
The Constitutional Court’s decision state that the authority to examine Perpu is a positive new development in constitutional law not just Indonesia that not only binds the parties, but the jurisprudence of the constitutional law in Indonesia, with the decision, to the possibility of abuse of power through Perpu and systemic weaknesses in the UUD 1945 in overseeing the president is to be anticipated product which itself also will give more legal protection for the seeker of justice, the ruling which states the The Constitutional Court’s authorities to examine Perpu in testing comes as the functioning of the judiciary as an organ which not only uphold the  law but also justice, by therefore, the decision was inspiring for judicial power in Indonesia to capitalize on his power to find justice.